The Ecological Value of Typical Agricultural Products: An Emergy-Based Life-Cycle Assessment Framework - Wang, Yongyang; Liu, Gengyuan; Cai, Yanpeng; Giannetti, Biagio F.; Agostinho, Feni; Almeida, Cecilia M. V. B.; Casazza, Marco (Frontiers in Environmental Science, 2022)
Agri-products have an impact on food security, ecology protection, and crucial strategic deployment. With this respect, the economic value of agri-products should be paralleled with a non-monetary assessment of ecological value for humans. This study set up an emergy-based life-cycle assessment (Em-LCA) framework to calculate the ecosystem service (ES) and ecosystem dis-services (EDS) that was applied to six typical crops, exploring the implementation path of the agricultural eco-product value. The results showed the agriculture system mainly depends on non-renewable resources. EDS generated by China’s agri-products is higher than the ES provided by them. Nevertheless, there is a low correlation between the current price of agri-products and their greenness, but, economic value presents a rising trend with agri-product greenness increasing. Further to discussing effective approaches to sustainable agriculture, it can be seen that 1) sustainable agriculture will lead to increased greenness, but it is impossible to improve greenness indefinitely. 2) Improving greenness is an effective way to implement ecological value, another way to preserve and raise ecological value is to reduce EDS generation. 3) Reducing energy consumption leads to a decrease in EDS but it is not an appropriate way to achieve sustainable development. These findings provide meaningful suggestions for decision-makers to realize the ecological value of agri-products.